2006
DOI: 10.1080/07420520601059615
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study of the Safety Implications of Australian Nurses' Sleep and Work Hours

Abstract: The frequency and severity of adverse events in Australian healthcare is under increasing scrutiny. A recent state government report identified 31 events involving "death or serious [patient] harm" and 452 "very high risk" incidents. Australia-wide, a previous study identified 2,324 adverse medical events (AME) in a single year, with more than half considered preventable. Despite the recognized link between fatigue and error in other industries, to date, few studies of medical errors have assessed the fatigue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
75
0
13

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(97 citation statements)
references
References 21 publications
9
75
0
13
Order By: Relevance
“…Participants in our study identified impairments in cognitive functioning and decision making when naps were desired but not possible, experiences congruent with findings that nurses were at increased risk for making and not catching errors during periods of sleep deprivation. 5 Similar to findings reported by Dorrian et al 5 and Scott et al, 8 nurses in our study reported risk for personal injury related to fatigue and specifically associated with the drive home after working the night shift.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Participants in our study identified impairments in cognitive functioning and decision making when naps were desired but not possible, experiences congruent with findings that nurses were at increased risk for making and not catching errors during periods of sleep deprivation. 5 Similar to findings reported by Dorrian et al 5 and Scott et al, 8 nurses in our study reported risk for personal injury related to fatigue and specifically associated with the drive home after working the night shift.…”
Section: Discussionsupporting
confidence: 81%
“…Nurses working nights are less alert and more likely to struggle to stay awake during the latter half of the shift than are nurses working permanent day or evening shifts. 39,40 In a study 5 …”
Section: Patient Safetymentioning
confidence: 99%
See 1 more Smart Citation
“…O exposto é reiterado em estudos, os quais demonstraram que a qualidade do sono noturno dos trabalhadores nas folgas é melhor do que a do sono diurno nos dias de trabalho e que a quantidade de horas de sono noturno nos dias das folgas é maior do que a quantidade de horas de sono diurno nos dias pós trabalho noturno (10)(11)(12) . Durante a pesquisa verificou-se que duas enfermeiras (Polaris e Hamal), trabalhadoras há mais de cinco anos do turno da noite e que são definitivamente vespertinas, desenvolveram hábitos de sono peculiares, isto é, na noite posterior ao seu plantão elas não conseguem dormir em horário dito "normal".…”
Section: O Sono Do Dia Não Tem a Qualidade Nem A Quantidade Do Sono Dunclassified
“…Working overtime has been associated with an increase of work-family conflict and stress if the shift is longer than 12.5 hours (Rogers, et al, 2004). Nurses on night shifts have reported high levels of stress, physical and mental exhaustion (Dorrian, et al, 2006). Another study among nurses reported that the nurses used http: //dx.doi.org/10.15405/epsbs.2016.11.02.11 eISSN: 2357-1330 responsibility of the Organizing Committee of the conference 110 their half an hour of break during the shifts to take a rest or meals (Rogers, et al, 2004).…”
Section: Introductionmentioning
confidence: 99%